BID-ASK SPREAD DAN PERIODE KEPEMILIKAN SAHAM PADA PERUSAHAAN LQ-45 - Maulina, Vinus; Rusno, Rusno (Jurnal Ekonomi Modernisasi, 2011)
Global crisis gives quite big impact to the Indonesian Stock Exchange and also changes the investor behavior as well. Fundamental exchange which is considered fragile becomes instability threat and reflects uncertain condition. This research aims to analyze and explain empirically the impact of variance return, trading volume, stock prices and return shares toward bid-ask spread which is the measurement of asymmetrical information cost, also the impact of variance return, market value, bid-ask spread and dividend pay out towards common shares holding periods in Indonesia Stock Exchange and some dominant variable that affect them.The findings of this research strengthen the presumption that in conducting the investment, investors in Indonesian Stock Exchange is more oriented to short term investment by expecting more on common shares than dividend. Most investors keep their ownership in common shares in Indonesian Stock Exchange for two years. Besides, the efficient investment strategy which optimizes profit is â€œswitching strategyâ€, following the market movement every time exactly, using technical information to active shares by moving from the shares that the price is predicted to decline to the increased ones. Moreover, the researcher also got the evidence that the investors in Indonesian capital market conduct their investment irrationally, investorâ€™s analysis is getting technical and gives less attention to the fundamental factors. The decision of selling and buying which is conducted by the investors on common shares is based on the trading activity, that is actually a measurement of the scale of asymmetry information.